Clinical outcome of preterm babies managed for respiratory distress syndrome using nasal continuous positive airway pressure and surfactant: An experience from Ile-Ife, South-Western Nigeria - Adejuyigbe, E; Ugowe, Osagie; Anyabolu, Chineme; Babalola, Toluwani (Journal of clinical neonatology, 2022)
Background: Respiratory distress syndrome (RDS) is a common cause of morbidity and mortality among preterm babies. It is caused by a deficiency of surfactant; hence, there is reduced lung compliance and increased work of breathing. The use of continuous positive airway pressure (CPAP) ventilation, a noninvasive form of ventilation, as well as the administration of exogenous surfactant, has proven to be very useful in the management of RDS. The use of less invasive techniques in ventilation and administration of surfactant have also been shown to reduce the risk of bronchopulmonary dysplasia and adverse effect of intubation. Objective: The objective is to determine mean oxygen saturation at 1 h, 6 h, and 12 h after commencement of CPAP, the mean values of FiO2 and positive end-expiratory pressure before and after administration of surfactant, and the overall case-fatality rate and birth weight-specific mortality rates. Methods: Study design was a prospective observational study and subjects were inborn babies between 26 and 34 weeks gestation who were managed for RDS with CPAP alone or with additional surfactant. Results: All 104 recruited preterm babies were managed with CPAP. Fifty-six (53.8%) babies also had surfactant administered. The mean weight of the babies was 1.35 (±0.322) kg, and the mean gestational age was 30.95 (±2.24) weeks. Extremely low birth weight (ELBW), very low birth weight (VLBW), and LBW constituted 11.5%, 55.8%, and 32.7% of the study population, respectively. The mean SPO2 before CPAP and 12 h after were 90.93 (±5.39) % and 96.5 (±3.30) %, respectively. The overall case-fatality rate was 18.2%, and birth-weight-specific mortality rates for ELBW, VLBW, and LBW were 58.3%, 15.5%, and 9.7%, respectively. Conclusion: From this study, it is clear that the prompt use of a cost-effective CPAP devices and the administration of surfactant are very effective in reducing morbidity and mortality among VLBW babies. While most local studies focused on the experience with the use of CPAP alone, this study goes further to demonstrate that the use of CPAP and surfactant is more effective in the management of RDS.